Diagnostic Accuracy of Urinary Biomarkers in Periodontitis: A Systematic Review and Meta-Analysis - Adriano Fratini; Rossana Izzetti; Nicola Riccetti; Stefano Gennai; Filippo Graziani; Enrico Marchetti (Hindawi Limited, 2024)
Background. Biomarkers can be measured in various biological samples. Urine is among the most useful biofluids for routine testing, and several experimental and clinical studies support its role as a tool for the diagnosis and prevention of various diseases. The present systematic review aimed to examine periodontitis-specific urine biomarkers that could have a diagnostic relevance and to provide a qualitative assessment of the current literature. Materials and Methods. Relevant studies identified from PubMed, Embase, Cochrane Library, and Scopus databases were examined to answer the following PECO question: "Could the concentration of specific metabolites in the urine be related to periodontal health and what is their diagnostic accuracy?". Quality of included studies was rated using ROBINS-I tool. Meta-analysis was conducted on available quantitative data. Results. After the screening of 768 titles, five studies were included in qualitative synthesis. The studies included referred to the evaluation of 8-hydroxy-2'-deoxyguanosine (8-OHdG) and neopterin. Meta-analysis was conducted for neopterin concentration on data available in four studies involving 129 participants. Higher concentrations of neopterin were found in periodontitis-affected patients compared to controls and patients treated for periodontitis. Conclusions. The literature appears controversial in attributing a role to neopterin and 8-OHdG as periodontal biomarkers, highlighting the need for further clinical studies on this topic. While some studies report variations in 8-OHdG and neopterin levels in periodontally affected patients versus either controls or periodontally treated patients, the level of evidence appears still limited to draw firm conclusions (PROSPERO CRD42020222681).